Pemikiran Pendidikan Ibnu Khaldun - Ina Zainah Nasution (UMSU, 2020)
Ibnu Khaldun was the greatest Muslim scientist of his time. His thoughts are futuristic and still be used for today. As a recognized scientist both in the West and in the East, we should take the wisdom points of his thinking in the field of education. Ibnu Khaldun set educational goals that are free from materialistic elements, an integrated curriculum and even holistic teaching and learning methods. Khaldun's view later in the 20th century, along with the development of contemporary learning psychology, we know him with the term gestalt psychology which was introduced by Wolfgang Kohler in 1912 in Germany. Khaldun's three steps in the delivery of teaching material are also in accordance with the theory issued by Kohlerberg about the maturity of one's cognition affecting one's ability to receive things. Therefore, to make closer to the true concept of Ibn Khaldun's education, the writer uses the method of content research which is to make Ibn Khaldun's monumental work: The Muqaddimah as the main reference and several other supporting books. So with this effort we can know that Ibn Khaldun was truly